Managerial Risk‐taking in International Acquisitions in the Brewery Industry: Institutional and Ownership Influences Compared. (31st January 2012) - Geppert, Mike; Dörrenbächer, Christoph; Gammelgaard, Jens; Taplin, Ian
Abstract : This paper deals with the role that institutional differences play in managerial risk‐taking when firms engage in international acquisitions. It is assumed that multinational corporations (MNCs) have different interests and capabilities when dealing with international acquisition, which in the authors' view are significantly shaped by specific home country institutional influences. This study concerns the question of how different forms of ownership – concentrated (e.g. family and bank based) and dispersed (stock market based) – influence risk‐taking and managerial decision‐making in large international acquisitions. Comparing a total of 12 large acquisitions of four leading MNCs in the global brewery industry, the paper shows that mutually reinforcing influences of country of origin (coordinated vs liberal market economies) and ownership (family ownership vs stock market ownership) lead to different risk profiles and managerial risk‐taking with regard to international acquisitions.